THE ARCHIVE OF THE WORKING GROUP OF THE MEMELLAND DISTRICTS IN CLOPPENBURG (GERMANY) AND THE INVENTORY DOCUMENTING MEMELLAND HOMELAND HISTORY - KLEIN, MANFRED (Knygotyra, 2015)
The “Archive of the Working Group of the Memelland Districts” is sustained by the umbrella organization of the former (mostly German speaking) Memelland inhabitants and their descendants – the “Working Group of the Memelland Districts e.V.” (“Arbeitsgemeinschaft der Memellandkreise”, AdM). The archive was founded in 1991 in the town of Cloppenburg in Lower Saxony by pooling several older collections and museum inventories. It is looked after exclusively in an honorary capacity, is located in a private house, and for this reason has limited accessibility. Due to a lack of space, a part of its inventory was relocated to Oldenburg in 2005, where it is also temporarily limited in use. In addition to its archival records, in a narrower sense the archive contains an extensive library in both the German and the Lithuanian language including literature from and about Memelland and the rest of East Prussia. All together, the inventory makes up to at least 100 shelf meters. The archive inventory consists of printed and hand-written documents, photographs and postcards, graphic artwork, water-colour paintings, films and video documentations as well as individual artefacts such as models etc. Among the printed objects worth mentioning in particular are older newspaper issues or single volumes of the 19th century from the city of Memel and Memelland. Among the hand-written documents there are extensive written reminders such as reports on events and autobiographies of a number of Memellanders. Not least of all of further historical interest are the complete documentations of the activity of the organization of Memelland expellees and their individual local groups dating back to 1948. It is planned to record a considerable part of the inventory electronically to also make it digitally visible and usable (internet). No decision, however, has yet been made concerning the future of the whole inventory.